Citizens' Attitudes Towards Local Services Accountability and Transparency: - Lejla Lazović Pita; Velma Pijalović; Lamija Šćeta; Almir Peštek (Central European Public Administration Review)
Purpose: The aim of this paper is to evaluate the perceived downward accountability and transparency of two public services – water supply and sewage and local road maintenance – in the Sarajevo Canton in Bosnia and Herzegovina (BiH). Design/Methodology/Approach: An opinion survey[1] on a sample of 250 respondents and four binomial regressions were conducted to measure the factors that affect the perceived downward accountability and transparency of the two public services. Findings: The results of binomial logit regressions indicate that in terms of perceived accountability and transparency of water supply and sewage, significant variables include gender, education, and satisfaction with the price the respondents pay for such service. Significant variables for perceived local road maintenance accountability include satisfaction with regular and winter local road maintenance, while for perceived transparency an additional significant variable is education. Academic contribution to the field: Although publications and literature dealing with the implementation of New Public Management in developed countries are plentiful, this is not the case in transition countries. The paper examines the case of the Sarajevo Canton and contributes to the research of perceived downward accountability and transparency. It may serve as a basis for further studies on public sector management in other local communities or small transition countries. Originality/Value: The paper contributes to the limited empirical literature regarding the perceived accountability and transparency and suggests ways to improve such.